2014
DOI: 10.1002/bdrc.21074
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest cells: From developmental biology to clinical interventions

Abstract: Neural crest cells are multipotent cells, which are specified in embryonic ectoderm in the border of neural plate and epiderm during early development by interconnection of extrinsic stimuli and intrinsic factors. Neural crest cells are capable of differentiating into various somatic cell types, including melanocytes, craniofacial cartilage and bone, smooth muscle, and peripheral nervous cells, which supports their promise for cell therapy. In this work, we provide a comprehensive review of wide aspects of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 115 publications
(130 reference statements)
0
22
0
Order By: Relevance
“…A potential explanation is that the aorta and intracranial arteries embryologically originate from the neural crest cells, and some anomalous development of these cells (neurocristopathy) could explain the susceptibility for both AA and IA. [18][19][20] However, despite the origin and susceptibility factors for AA and IA, their origin is probably a combination of genetic and environmental factors. Furthermore, our study identified a prevalence of IAs in the AA population 4 times higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation is that the aorta and intracranial arteries embryologically originate from the neural crest cells, and some anomalous development of these cells (neurocristopathy) could explain the susceptibility for both AA and IA. [18][19][20] However, despite the origin and susceptibility factors for AA and IA, their origin is probably a combination of genetic and environmental factors. Furthermore, our study identified a prevalence of IAs in the AA population 4 times higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The multipotent neural crest cells are able to undergo epithelial to mesenchymal transition and migrate to many body locations. Soon after the initiation of the migratory process, neural crest cells commit to progressively restricted cell lineages, finally differentiating into a variety of cell types, including the peripheral nervous system (neurons, glial cells, and Schwann cells), endocrine and paraendocrine cells, melanocytes in the epidermis, craniofacial cartilage, bone and connective tissue [95,96]. During this process, cell fate seems to be regulated by both positional signals and extracellular ligands.…”
Section: Mycn and Embryonic Tumorsmentioning
confidence: 99%
“…Multiple cell lineages contribute to the developing heart. Neural crest cells (NCCs) are multipotent, migratory cells that arise from the dorsal neural tube (Noisa and Raivio ). Cardiac NCC migrate into the heart through the caudal pharyngeal arches (PAs) to septate the outflow tract (OFT), to form a patent aorta and pulmonary artery, as well as contribute to pulmonary and aortic valves (Keyte and Hutson ).…”
Section: Cardiac Morphogenesismentioning
confidence: 99%